Phase Evolution and Electrical Characterization of Bismuth Vanadate - Tahir, Z.; Rashid, M. U.; Ahmad, S. (The Nucleus, 2018)
In the present study, phase, microstructure and electrical properties of BiVO4 sample prepared by solid state sintering route have been studied. Phase analysis of the sintered sample revealed the formation of single phase BiVO4with no evidence of the secondary phase within the detection limit of X-ray diffractometer. Furthermore, the crystal structure was investigated by Rietveld analysis which confirmed the monoclinic symmetry having lattice parameters a = 7.2478 Å, b = 11.695 Å, c = 5.0919 Å and ? = 134.255°. SEM micrographs showed dense and irregular shaped grains with sizes ranging from 1.2 µm to 15.2 µm. Dielectric properties as a function of temperature for the BiVO4 sample exhibited phase transition at three different temperatures (~69°C, ~280°C and ~465°C). The dielectric loss increases with increasing temperature, indicating the semiconducting like features at higher temperatures which were further confirmed using impedance spectroscopy data.